Lean culture assessment in manufacturing industry: a case study advanced composites manufacturing industries - Moustapha Mahamat Moussa Adam (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Manufacturing organizations are under pressure to improve productivity and reduce costs through the realization of lean culture. This paper approaches lean culture and aims to identify and measure the closely related parameters of lean culture and also examines the weight of their contribution to overall lean culture. The methodology approach is a questionnaire survey study was performed in advanced composites manufacturing industries to collect data.